Analisis Butir Soal Pilihan Ganda Mata Pelajaran Ekonomi Bisnis dan Administrasi Umum dengan Menggunakan Aplikasi Software Anates di SMK NU Gresik - Rosita Dewi Iriyanti; Najwa Dafa Agustina; Dini Aulia Prinita; Luqman Hakim; Vivi Pratiwi (PADMA, 2024)
This research is motivated by the importance of quality learning evaluation in measuring the achievement of student competencies. The main purpose of this research is to analyze the quality of multiple choice items in Business Economics and General Administration subjects using the Anates software application. The research method used is quantitative descriptive using data collection techniques through google form. Obtained high test reliability value data, which showed a number of 0.72. There is a division of superiors group consisting of 5 students who have high scores and asor group consisting of 5 students with low scores. The Discriminating power in working on multiple choice questions is quite good, while the quality of the problem distractors as a whole is less effective and has not functioned properly. Thus, overall the multiple choice questions on Business Economics and General Administration subjects are significant and appropriate to be given to students.